Augmented Reality-Based Furniture Catalog Design - เครือแดง วริศ; พุ่มช่วย ศุภพล; เฉลิมแสน สรวิศ; นาคสุข พุทธินันท์; ทองติ่ง ทองติ่ง (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to: 1) design and develop a furniture catalog utilizing Augmented Reality (AR) technology, and 2) evaluate user satisfaction with the developed AR-based furniture catalog. The sample group consisted of 30 consumers in the Bangkok Metropolitan Region who were interested in purchasing furniture and capable of using AR technology via smartphones. Participants were selected through purposive sampling, focusing on individuals with prior experience in furniture purchasing who voluntarily participated in the system testing. The research instruments included: 1) the Augmented Reality-based furniture catalog, 2) an efficiency evaluation form for experts, and 3) a user satisfaction questionnaire. The research results indicated that the efficiency evaluation by experts was at a high level, with a mean score of 4.21 and a standard deviation of 0.60. Furthermore, the user satisfaction evaluation revealed a high overall satisfaction level, with a mean score of 4.30 and a standard deviation of 0.58. Consequently, it can be concluded that the design of a furniture catalog using Augmented Reality technology is highly applicable to furniture retail businesses. It enhances product attractiveness, provides an innovative customer experience, and promotes a modern corporate image aligned with the digital era.